Initial Study: The Effect of Digital Literacy on Students' Argumentation Skills in Junior High School on the Materials of Motion, Waves and Light - Septiani, Neni; Darmaji, Darmaji; Kurniawan, Dwi Agus (Indonesian Journal of Education and Mathematical Science, 2024)
The purpose of this study was to determine the effect of digital literacy on students' argumentation skills in junior high school on vibration, wave and light materials. The method used in this research is a qualitative method, with the type of research using an initial study obtained by interview, the subjects and samples of this study were science teachers at Muaro Jambi State 1 Junior High School and Muaro Jambi State 33 Junior High School, the sampling technique in this study was purposive sampling technique, the instrument used was an interview with 20 questions, the data analysis used was Mile and Huberman analysis. Based on the research that has been done, the results show that digital literacy can improve students' argumentation skills. So the conclusion of this study is that digital literacy has an influence on students' argumentation skills.